Participatory plant breeding to develop biofortified upland rice for marginal environments - Castro-Pacheco, Sergio Antonio; Rabekijana, Ravo; Andriamiarana, Mahevanirina; Raveloson, Harinjaka; Rakotomalala, Joël; Ramanantsoanirina, Alain; Garin, Vincent; Grenier, Cecile; vom Brocke, Kirsten (Cambridge University Press, 2024)
Abstract In the Highlands of Madagascar, where rice is the main staple food, explosive demographic growth has driven the need for the development of upland rice. In that context, a Participatory Plant Breeding (PPB) program conducted by the FOFIFA-Cirad partnership, aims to develop upland rice varieties adapted to farmers’ needs, with superior agronomic performances, and with high grain zinc concentration. In the area, where ferralitic soils with N and P deficiencies prevail, limited fertilizer usage persists due to elevated costs, and upland rice varieties must adapt to these low fertility environments. Thus, this paper aims to identify the adequate selection conditions and methods that allow combining the above-mentioned criteria for selection. So, 56 rice breeding lines, including high-zinc genotypes, were evaluated in field trials with contrasting fertility conditions. A relative selection efficiency analysis demonstrated that selection for yield should be done in moderate fertility environments, while selection for grain zinc concentration could be done across a diverse range of conditions. Through participatory evaluations, we identified that, for this case, grain appreciation was the most important character for deciding whether to select a line, followed by productivity and earliness. We also noted that farmers were more willing to accept a variety if it had higher grain zinc concentration. Finally, we proposed a selection index that combines agronomic, farmers’ and nutritional criteria, with the purpose of selecting lines that fulfill the expectations on these areas. Overall, this paper proposes an adapted methodology for the combination of PPB and biofortification in marginal environments.